(untitled) (Prostor, 2021)
In the period of Austro-Hungarian occupation between 1878 and 1918, the City of Mostar had a process of intensive urbanization. In that period, newly arrived engineers (surveyors) transformed the pre-existing Eastern – Ottoman qasaba (provincial town) into a Central European city. This paper revealed four models of urbanization they used in planning. The first model was developed within the existing physical structure of the city through the first regulatory plan. The second model forms the new urban centre using the empty space within the old town. The third and the fourth models expand the city over the river. While the third model forms orthogonal urban blocks, the fourth is a construction of free-standing villas within the Neo-Baroque Square in which six radial streets inflow. The engineers who worked on the regulatory plans were also discovered and presented, as well as the legislative and legal framework within which all these processes took place.